Clarifying the role of officer coping on turnover in corrections - Harney, Jessie (Criminal justice studies, 2021)
Correctional officers are at high risk of exposure to workplace violence, and many report experiencing severe mental health symptoms, including post-traumatic stress disorder, anxiety, and depression. Despite growing concern for these issues, however, we do not yet fully understand the coping mechanisms correctional officers employ to manage work-related stress, or how coping mechanisms affect workplace outcomes. To address these questions, we utilize original survey data about California correctional officers. We draw on the Stress Process Paradigm to model the relationship between exposure to violence and mental health, the impact of occupational stress on the development of coping mechanisms, and whether differential coping mechanism utilization impacts officers’ levels of cynicism and desire to leave corrections. Our findings suggest that emotion-focused coping (e.g. having someone to talk to) is associated with lower intention to leave correctional employment, while the opposite is true for avoidant coping (i.e. alcohol abuse). These insights shed light on the problem of officer turnover and retention, and provide potential direction to policymakers and practitioners seeking to create an effective, healthy workforce.